Research on the parameters influencing the thermal conductivity of gypsum plasterboard under fire conditions. Issue 1 (1st January 2019) - Vo Thong, Nguyen; Hung, Tran
Abstract: In Vietnam, the fire protection for steel structures is relativity much; thus, the study of fire protection solutions for the load-bearing steel structures (beams, columns) is considered very important in the safety of the buildings. One possible solution is the use of gypsum plasterboard. Up to now, the engineers use the constant thermal conductivity to verify the fire resistance of steel structures protected by gypsum plasterboard. However, the thermal conductivity depends on many factors such as temperature, moisture, thickness, type of plasterboard, manufacturer, heating rate. This paper presents an experimental identification of the thermal conductivity of gypsum plasterboard fabricated under fire conditions.